Ultimate Full-Stack Web Development with MEVN: Learn from Designing to Deploying Production-Gr7ade Web Applications with MongoDB, Express, Vue, and Node. js on AWS, Azure, and GCP (English Edition) - Bachina, Bhargav (Orange Education PVT Ltd, 2024)
Embark on a journey into modern web development with the Ultimate Full Stack Web Development with MEVN to build robust, scalable applications using MongoDB, Express.js, Vue.js, and Node.js. Starting with fundamental concepts and installation steps, this book progresses to advanced topics and hands-on coding exercises, culminating in the creation of a comprehensive project that spans the entire stack. The book will dive into Vue.js for crafting seamless dynamic user interfaces and explore Node.js modules and components to effectively structure applications. Next, it will delve deeper into MongoDB for efficient data management and seamless integration within your MEVN stack. It will navigate UI development intricacies and explore essential logging options to refine Node.js API development practices. In the concluding section, you'll learn essential techniques for deploying MEVN applications effectively in production environments. The book will cover Docker's capabilities for consistent application containerization across varied deployment settings and critical unit testing and end-to-end testing strategies to boost application reliability and performance. By the end of the book, you will be able to deploy and scale your MEVN apps on cloud platforms like Google Cloud, AWS, and Azure.